Effects of natural additives on the production of genetically stable vitroplants: Application to Aloe (Aloe vera L.) - Hamdeni, Imtinene (National Research Institute of Rural Engineering, Water and Forest, 2023)
The micropropagation is currently adopted as a reliable process for mass vegetative multiplication of plants. However, several plants still face various challenges in this method, such as enzymatic browning, as well as fungal and bacterial contaminations. To overcome these challenges, the incorporation of natural organic additives into the culture medium is considered of great interest by some researchers for the success of in vitro multiplication protocols due to their antioxidant, antifungal, and/or nutritional properties. This study aims to evaluate the effects of using natural compounds on the in vitro multiplication of a plant sensitive to the mentioned problems, specifically Aloe vera L. Thyme (Thymus vulgaris L.) and rosemary (Rosmarinus officinalis L.) essential oils (EO) were used to control enzymatic browning and fungal contaminations, while Aloe vera leaf gel (AvG) was used as a nutritional supplement in the proliferation phase. Considering that in vitro multiplication can lead to vitrovariation, the genetic stability of the produced Aloe vera vitroplants was verified using DNA-based molecular markers. Observations showed that while thyme EO inhibits explant growth, rosemary EO allows the survival of explants at a percentage of 100%, after 4 weeks of culture with concentrations of 0.05, 0.075, and 0.1% without any sign of browning. The lowest infection percentage (10%) was obtained on media containing 0.075 and 0.1% rosemary EO. For explant multiplication, the highest number of axillary shoots recorded was 13.27 ± 5.11 with an average length of 2.21 cm ± 0.84 on MS medium supplemented with 5% AvG. The MS mineral salts concentration (1, 1/2, 1/4) combined with different concentrations of AvG (10, 20, 30%) resulted in 100% root induction after 4 weeks of culture. All produced vitroplants were successfully acclimatized. The genetic stability of Aloe vera vitroplants was evaluated using 10 ISSR (inter simple sequence repeat), 10 SCoT (start codon targeted), and 10 SSR (simple sequence repeat) markers. Among these markers, 5 ISSR primers, 3 SCoT, and 6 SSR produced reproducible and evaluable bands. ISSR primers generated 32 amplification products ranging from 200 to 1040 bp with an average of 6.4 bands, while SCoT primers generated 33 amplicons with an average of 11 bands in the size range of 160 to 2410 bp. In the SSR products, 6 bands were observed, each primer producing a band ranging from 410 to 720 bp. All band profiles were monomorphic, proving that the genetic identity of Aloe vera vitroplants is preserved. A comparative analysis of ethanol extracts from the cuticle, gel, and exudate of Aloe vera was conducted. The results showed that the ethanol extract of Aloe vera exudate was the richest in phenolic compounds, while the gel exhibited the best antioxidant properties. Quercetin pentoside-glucuronide is the main constituent of the gel, while Aloe emodin dianthrone di-O-hexoside is the main constituent of the cuticle and exudate, respectively. French: La micropropagation est adoptée, aujourd’hui, comme un procédé fiable de multiplication végétative en masse des végétaux. Cependant, cette voie reste confrontée, chez plusieurs végétaux, à différents handicaps comme le brunissement enzymatique ainsi que les contaminations fongiques et bactériennes. Pour surmonter ces handicaps, l'incorporation dans le milieu de culture d'additifs organiques naturels, est selon certains chercheurs, d’un grand intérêt pour la réussite du protocole de multiplication in vitro en raison de leurs propriétés antioxydantes, antifongiques et/ou nutritives. Dès lors, le présent travail a été conduit pour évaluer les effets de l’utilisation de composés naturels sur la multiplication conforme in vitro d’une plante sensible aux problèmes cités, en l’occurrence, Aloe vera L. A cet effet, les huiles essentielles (HE) de thym (Thymus vulgaris L.) et de romarin (Rosmarinus officinalis L.) ont été utilisées pour contrôler le brunissement enzymatique et les contaminations fongiques alors que le gel de feuilles d'Aloe vera (AvG) a été utilisé comme supplément nutritif en phase de prolifération. Considérant que la multiplication in vitro peut être à l’origine de vitrovariation, la stabilité génétique des vitroplants d'Aloe vera produits a été vérifiée en utilisant des marqueurs moléculaires à base d'ADN. Les observations réalisées ont montré que si l'HE de thym inhibe la croissance des explants, celle de romarin permet la survie des explants à un pourcentage de 100 %, après 4 semaines de culture avec des concentrations de 0,05, 0,075 et 0,1 % sans aucun signe de brunissement. Le pourcentage d'infection le plus faible (10 %) est obtenu sur les milieux contenant 0,075 et 0,1 % d'HE de romarin. Pour la multiplication des explants, le nombre le plus élevé de pousses axillaires enregistré est de 13,27 ± 5,11 avec une longueur moyenne de 2,21 cm ± 0,84 sur le milieu MS additionné de 5 % d’AvG. La concentration des sels minéraux MS (1, 1/2, 1/4) combinée à différentes concentrations d'AvG (10, 20, 30%) a entraîné une induction racinaire de 100% après 4 semaines de culture. Tous les vitroplants produits ont été acclimatés avec succès. La stabilité génétique des vitroplants d'Aloe vera a été évaluée à l'aide de 10 marqueurs ISSR (inter simple sequence repeat), 10 marqueurs SCoT (start codon targeted) et 10 marqueurs SSR (simple sequence repeat). Parmi ces marqueurs, 5 amorces ISSR, 3 SCoT et 6 SSR ont produit des bandes reproductibles et évaluables. Les amorces ISSR ont généré 32 produits d'amplification allant de 200 à 1040 pb avec un nombre moyen de 6,4 bandes tandis que les amorces SCoT ont généré 33 amplicons avec une moyenne de 11 bandes dans la taille de 160 à 2410 pb. Dans les produits SSR, 6 bandes ont été observées, chaque amorce a produit une bande allant de 410 à 720 pb. Tous les profils de bandes étaient monomorphes prouvant que l’identité génétique des vitroplants d’Aloe vera est préservée. Une analyse comparative des extraits éthanoliques de la cuticule, du gel et de l'exsudat d'Aloe vera a été réalisée. Les résultats ont montré que l'extrait éthanolique de l'exsudat d'Aloe vera était le plus riche en composés phénoliques, tandis que le gel présentait les meilleures propriétés antioxydantes. Le pentoside-glucuronide de quercétine est le principal constituant du gel tandis que l'Aloe émodine dianthrone di-O-hexoside est le principal constituant de la cuticule et de l'exsudat respectivement.